Novel Insights Into Mesothelioma Therapy: Emerging Avenues and Future Prospects - Kuryk, Lukasz; Rodella, Giulia; Staniszewska, Monika; Pancer, Katarzyna Wanda; Wieczorek, Magdalena; Salmaso, Stefano; Caliceti, Paolo; Garofalo, Mariangela (Frontiers in Oncology, 2022)
Malignant mesothelioma is a rare and aggressive cancer that develops in the thin layer surrounding the mesothelium and is mainly caused by asbestos exposure. Despite improvements in patient prognosis with conventional cancer treatments, such as surgery, chemotherapy, and radiotherapy, there are still no curative treatment modalities for advanced disease. In recent years, new therapeutic avenues have been explored. Improved understanding of the mechanisms underlying the dynamic tumor interaction with the immune system has led to the development of immunotherapeutic approaches. Numerous recent clinical trials have shown a desire to develop more effective treatments that can be used to fight against the disease. Immune checkpoint inhibitors, oncolytic adenoviruses, and their combination represent a promising strategy that can be used to synergistically overcome immunosuppression in the mesothelioma tumor microenvironment. This review provides a synthesized overview of the current state of knowledge on new therapeutic options for mesothelioma with a focus on the results of clinical trials conducted in the field.